The Intellectual Conscience of Art - Balkema, Annette W.,; Slager, Henk, (Lier & Boog ;, 1995)
At the core of this issue is the question of the concept of art. Could the task of art be transfered to philosophy, as Arthur Danto maintains? Or is there still a moral assignment for art inherent to Modernism? Various artists and theorists will respond to these questions in this issue. Among them are: J.C. Ammann, Victor Burqin, Don Cameron, Arthur Danto, Catherine David, Chris Dercon, Marlene Dumas, Jan Hoet, Joseph Kosuth, Donald Kuspit, Pieter Laurens Mol, Maarten van Nierop, A.B. Oliva, Frank Reynders and Haim Steinbach.